Rhinitis and Meningitis in Two Shelter Cats Caused by Streptococcus equi subspecies zooepidemicus - Britton, A.P. (J Comp Pathol, 2010)
In the past 6 years there have been increasing reports describing outbreaks of a severe fatal respiratory disease associated with Streptococcus equi subspecies zooepidemicus (SEZ) in dogs maintained in shelters, research facilities and kennels. Although SEZ appears to be an emerging pathogen of dogs kept in intensively housed environments, this bacterium has not been reported as a cause of death in intensively housed cats. This report describes fatal SEZ infection in two adult cats housed in separate animal shelter facilities. Both cats had acute onset of illness, which progressed to death in less than 24 h. Post-mortem examination revealed rhinitis and meningitis and SEZ was demonstrated in the nasal cavity and brain. Polymerase chain reaction and sequence analysis of a 500 base pair region of the 16S rRNA gene confirmed the identity of the bacterium.